Sistem Informasi Pengelolaan Bantuan Sosial Berbasis Mobile Menggunakan Metode Waterfall - Muh Indra Tri Kusuma; Rodhiyah Mardhiyyah (Bulletin of Computer Science Research, 2025)
The Banyuurip Village Office in Temanggung Regency still faces challenges in managing social assistance data and inventory, which are handled manually through physical record books. This condition causes the data verification process to be slow, prone to errors, and difficult to trace. This study aims to develop a mobile and web based information system for managing social assistance and inventory to improve administrative handling at the village level. The system development adopts the Waterfall method, consisting of requirement analysis, design, development, and testing stages. The system was built using Flutter as the primary framework and Firebase as a centralized NoSQL database to support data synchronization. System testing was conducted using the Black Box Testing method to ensure that the system’s functionalities operate according to the design. The test results indicate that all core features including social assistance data management, QR Code based recipient verification, and supporting features such as inventory management have met all predefined test scenarios. The mobile system is used by field staff responsible for performing on-site data recording, while the web system is operated by administrative staff for data management tasks. Both platforms were able to replace manual processes and enhance the smoothness and accuracy of administrative management within the village office.